Toleransi Umat Beragama dalam Tantangan Post Modern di SMP Negeri 2 Sei Menggaris - Endik Firmansah; Lena Anjarsari Sembiring (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
This study examines religious tolerance in a post-modern context at Sei Menggaris State Junior High School 2. This research examines how students, teachers and school policies play a role in promoting religious harmony amidst the challenges of the post-modern era. This study also explores the main challenges faced and effective strategies for strengthening religious tolerance in the school environment. This research uses a qualitative approach to understand the dynamics of religious tolerance at Sei Menggaris 2 State Junior High School. A qualitative approach was chosen because it allows researchers to explore an in-depth understanding of the attitudes, perceptions and experiences of students and teachers regarding religious tolerance. With this method, if the right policies, inclusive education and support from all communities in schools are produced, inter-religious harmony can be realized even in the midst of post-modern challenges.